Preoperative Ultrasound-guided Percutaneous Cryoneurolysis for the Treatment of Pain after Mastectomy: A Randomized, Participant- and Observer-masked, Sham-controlled Study. (5th August 2022) - Ilfeld, Brian M.; Finneran, John J.; Swisher, Matthew W.; Said, Engy T.; Gabriel, Rodney A.; Sztain, Jacklynn F.; Khatibi, Bahareh; Armani, Ava; Trescot, Andrea; Donohue, Michael C.; Schaar, Adam; Wallace, Anne M.
Abstract : Background: Ultrasound-guided percutaneous cryoneurolysis is an analgesic technique in which a percutaneous probe is used to reversibly ablate a peripheral nerve(s) using exceptionally low temperature, and has yet to be evaluated with randomized, controlled trials. Pain after mastectomy can be difficult to treat, and the authors hypothesized that the severity of surgically related pain would be lower on postoperative day 2 with the addition of cryoanalgesia compared with patients receiving solely standard-of-care treatment. Methods: Preoperatively, participants at one enrolling center received a single injection of ropivacaine, 0.5%, paravertebral nerve block at T3 or T4, and perineural catheter. Participants subsequently underwent an active or sham ultrasound–guided percutaneous cryoneurolysis procedure of the ipsilateral T2 to T5 intercostal nerves in a randomized, patient- and observer-masked fashion. Participants all received a continuous paravertebral block with ropivacaine, 0.2%, until the early morning of discharge (usually postoperative day 2). The primary endpoint was the average pain level measured using a 0 to 10 numeric rating scale the afternoon of postoperative day 2. Participants were followed for 1 yr. Results: On postoperative day 2, participants who had received active cryoneurolysis (n = 31) had a median [interquartile range] pain score of 0 [0 to 1.4] versus 3.0 [2.0 to 5.0] in patients given sham (n = 29): difference –2.5 (97.5% CI, –3.5 to –1.5), P < 0.001. There was evidence of superior analgesia through month 12. During the first 3 weeks, cryoneurolysis lowered cumulative opioid use by 98%, with the active group using 1.5 [0 to 14] mg of oxycodone compared with 72 [20 to 120] mg in the sham group ( P < 0.001). No oral analgesics were required by any patient between months 1 and 12. After 1 yr chronic pain had developed in 1 (3%) active compared with 5 (17%) sham participants ( P < 0.001). Conclusions: Percutaneous cryoneurolysis markedly improved analgesia without systemic side effects or complications after mastectomy. Abstract : A randomized trial design was used to compare analgesic requirements after breast surgery in those receiving paravertebral anesthetic blocks to those receiving the same blocks plus intercostal cryoneurolysis. Patients receiving cryoneurolysis reported less pain on postoperative day 2 suggesting benefit of this treatment.